The transformation of urban industrial land use: A quantitative method - Rongxu Qiu; Wei Xu; John Zhang (Journal of Urban Management, 2015)
A large number of cities around the world today owe their land use growth to the rapid development of industrial areas. The spatial structure of industrial distribution in cities shape urban spatial morphology linking with land use, transportation, economic activities, and housing. Meanwhile, growth and expansion of city population and land use reconfigure the spatial structure of industrial distribution. Research into urban industrial spatial distribution and its transformation process may help urban planners and decision makers understand the land use and population dynamics of a city. Genetic algorithms are believed to be one kind of the promising methods to simulate this dynamic process. In this paper, we propose a novel method to simulate urban industrial spatial distribution and its transformation process in Shanghai, China. The results show that along with increasing urban land price over time, industries are going to move outward from the city center. However, the maximum profit of a firm tends to decrease, which could lead industrial factories to move beyond city boundary. The analysis of the current industrial spatial distribution in Shanghai indicates that, when land price in a city rises above a specific threshold, new government policies and other competitive advantages need to be enacted if the city wants to retain industrial firms within the city boundary.
Keywords: 710; Genetic algorithm; Industrial spatial structure; Shanghai; Spatial analysis